Geophysical contribution to evaluate the hydrothermal potentiality in egypt: case study: hammam faraun and abu swiera, sinai, egypt (2010)
The geothermal potentiality in Egypt has a minor significance in the aspects of the Egyptians life, while the hydraulic and hydrocarbonresources are more convenient. However, some other applications for the geothermal activity such as direct warming, pools, and physiotherapy make the research for geothermal as requested. In the present work, two locations with rather good geothermal potentiality will be studied; these are HammamFaraun and Abu Swiera (water temperature is about 70 °C; at Sinai Peninsula).The contribution of the geophysical techniques to evaluate such potentiality could be considered, as its capability to identifythe reservoir characteristics and its implementation is acceptable. Therefore, a geophysical survey program has been conductedin terms of seventeen vertical electrical soundings (VES) and two wide profiles of Control Source Electromagnetic (CSEM) forward step at HammamFaraun and two wide profiles of CSEM at Abu Swiera. The geophysical techniques yield information on the spatial distribution of electrical conductivity, which is the most sensitive parameter to fluids in the rocks. The analysis of the geophysical data, together with the field and geochemical studies lead to the conclusion that, the thermalwater in the subsurface formations might be considered as the preferred cause of the high conductivity in the subsurface on/close to the boarder of tectonically active regions, particularly, where the anomalous conductivity is correlated with high heat flow and other geophysical and geological parameters.